Pengaruh Foreign Branding Terhadap Minat Beli Yang Dimediasi Oleh Persepsi Kualitas Produk Luxcrime: Studi Pada Mahasiswa Prodi Manajemen Fakultas Ekonomi Dan Bisnis Universitas Negeri Makassar - Elsafitri Elsafitri; Burhanuddin; Muhammad Ichwan Musa; Zainal Ruma; Ilma Wulansari Hasdiansa (Lembaga Pengembangan Kinerja Dosen, 2024)
The cosmetic industry in Indonesia has experienced rapid development with the emergence of various local and global cosmetic brands. Therefore, every cosmetic company needs to have a strategy to capture the market. One of the strategies that can be used is foreign branding which involves giving brand names using foreign languages aimed at influencing brand image dimensions, consumer perceptions, and attitudes towards the products. This research aims to determine the influence of foreign branding on purchase intention mediated by perceived product quality of Luxcrime products. This study is a quantitative research with a descriptive approach. The sample used consists of 100 students majoring in Management at the Faculty of Economics and Business, State University of Makassar. Data collection was conducted through literature study and survey. The data analysis technique used is Partial Least Square (PLS) analysis. The results of the study indicate that foreign branding does not have a positive and significant effect on purchase intention of Luxcrime products, foreign branding has a positive and significant effect on perceived product quality of Luxcrime products, perceived product quality has a positive and significant effect on the purchase intention of Luxcrime products and perceived product quality mediates the relationship between foreign branding and purchase intention of Luxcrime products